Frontispiece: Utilizing Palladium‐Stabilized Zwitterions for the Construction of N‐Heterocycles. Issue 56 (9th October 2017) - Allen, Benjamin D. W.; Lakeland, Christopher P.; Harrity, Joseph P. A.
Abstract : Pd catalysis provides a convenient method for the generation of zwitterionic intermediates that offer significant opportunities for the synthesis of functionalized heterocycles. The combination of electrophilic π‐allyl Pd fragments and C‐, N‐ and O‐centered nucleophiles allows these intermediates to react with readily available substrates to furnish a range of high value products with control of chemo‐, regio‐ and stereo‐selectivity. For more details see the Review article by J. P. A. Harrity et al. onpage 13830 ff.